Bryophytes from the area drained by the Peel and Mackenzie rivers, Yukon and Northwest Territories, Canada - Bird, Charles D.; Scotter, George W.; Steere, William C.; Marsh, Alfred H. (Canadian Journal of Botany, 1977)
The distribution and general ecology of 263 bryophyte taxa are presented for an extensive area of coniferous forest, open fens, and alpine terrain along the Mackenzie River in the District of Mackenzie and the Peel River, a major tributary which extends into the Yukon. The continuous or discontinuous permafrost which underlies the area plays a major role in determining the vegetational communities that are present. Fire and disturbance by man initiate succession. Thirty-nine liverworts, 20 peat mosses, and 204 true mosses are reported. There are 43 new reports for the District of Mackenzie and 16 for the Yukon. Cynodontium glaucescens is new to North America. Brachythecium glaciale, B. mildeanum, and B. trachypodium are confirmed for North America. Of the taxa 94.7% are found in Europe and Asia as well as North America, 4.2% are known only from Asia and North America, whereas only 1.1% are restricted to North America. High mountains in the western part of the area, generally nonglaciated during the Wisconsinan, support a flora that contains many Arctic and Arctic–Alpine taxa.